Film as an educational tool in medical pedagogy: a study on cinemeducation and its effectiveness - Cheema, Usama Naveed; Sarmed Ibrahim; Nukhbat Ullah Awan; Haram Ashiq; Wagma Sarmed; Khalid Munir (Journal of the Pakistan Medical Association, 2024)
Objective: To find out the possibilities and usefulness of introducing cinemeducation in medical institutions, and to formulate suggestive inserts for faculty and policy-makers. Methods: The quantitative study was conducted in Lahore from January to June 2021 after approval from the ethics review committee of King Edward Medical University, Lahore, and comprised fourth and final year medical students. Relevant short clips from seven movies of different genres were selected and shown to the students who were then divided into eight equal groups. Every session lasted 30 minutes, and was followed by an interactive discussion between the students and faculty members. The critical aspects of the sessions were discussed and analysed. Data was collected using a 7-item questionnaire that was scored on a 5-point Likert scale. Data was analysed using SPSS 21. Results: Of the 240 participants, the questionnaire was returned duly filled by 219(91.25%). Among them, 176(80.4%) said they found the experience worthwhile and that they would like to have such an experience again, while 184(84%) said such sessions should be made a part of regular curriculum. Also, 166(75.8%) participants felt that the session had helped them learn about crucial features of medicine, and 169(77%) thought that the session facilitated the understanding towards patient management. Conclusion: Cinemeducation was found to be an excellent tool of pedagogy that should be incorporated in all the relevant disciplines of medicine and allied sciences. Key Words: Cinemeducation, Methodology, Curriculum.